The SAGE handbook of feminist theory - Evans, Mary (SAGE reference, 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: Epistemology and marginality; Literary, visual and cultural representations; Sexuality; Macro and microeconomics of gender; Conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think ‘theoretically’ is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism. It is an essential reference work for advanced students and academics not only of feminist theory, but of gender and sexuality across the humanities and social sciences.
Keywords: approches et analyses; corps; cours; discipline; har4600; histoire et politique; intersectionnalité; outils; ouvrages de références; philosophie; phénoménologie; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences de la gestion; sciences humaines; sciences sociales; sex1911; thématiques; violences; économie; épistémologie; études féministes

Le travail social: théories, méthodologies et pratiques - Dorvil, Henri; Harper, Elizabeth; Bibliothèque numérique canadienne (Firme) (Collection Problèmes sociaux & interventions sociales, 2013)
"Ce livre vise à introduire de nouvelles façons de concevoir, de théoriser et d'intervenir sur le social en ce xxie siècle. Il y est non seulement question des fondements du travail social, mais aussi des politiques sociales, des méthodes d'intervention et des enjeux contemporains de la profession. En revisitant d'une manière créative les postulats de base du travail social, les auteurs proposent des lectures inédites des problèmes sociaux, un regard plus nuancé sur les populations marginalisées, un renouvellement des politiques sociales comme levier de citoyenneté ainsi que des pistes d'intervention plus respectueuses des individus, des groupes, des familles et des communautés."-- Site de l'éditeur.
Keywords: approche interculturelle; approches et analyses; cours; discipline; histoire et politique; intersectionnalité; outils; ouvrages de références; premier cycle; sciences humaines; sciences sociales; sex2283; thématiques; travail; travail social